An investigation into the implementation of the National Policy on District Support Services for effective teaching and learning at school level - Masipa, Mokgadi Maggie (My University, 2005)
This study examines the extent to which education districts in the Limpopo Province support effective teaching and learning at school level, with general applicability to similar education districts in South Africa and elsewhere. The literature reveals that education districts in most developing countries, do not support the participation of principals and educators, and that changes are required to effect higher levels of involvement. The study focuses on how this might be attained. The study makes recommendations on District Support Services which will ensure the involvement of district personnel, principals and educators in transforming schools into effective teaching and learning organisations. The theoretical base is derived from literature review on district support services in South Africa and elsewhere. This review is used to establish common conceptions for the study, and illustrates the extent to which the involvement of all relevant stakeholders is considered desirable and feasible. The analysis also reveals how the policy on district support services in South Africa falls short of complying with the country's local diversity and also with its policy of Outcomes - Based Eduaction which focuses on producing citizens who are equipped with values, knowledge and skills that will enable them to play a productive role in society. The implication of Outcomes - Based Eduaction is that individuals acquire these qualities through active involvement in the learning process. It seeks to create a lifelong learner who is confident and independent, literate and multi-skilled, compassionate, with respect for the environment and the ability to participate in society as a critical and active citizen. The field work was carried out in education institutions falling under Sekgosese Education District in Region Three of Limpopo Province and involved a sample of three hundred and thirty-two education practictioners, divided into five target groups:educators (200), principals (100), circuit managers (4), curriculum advisers (16), and administrators (12). The analysis of the data is composed of three parts. The first concerns the calibre of people who are implementing the policy. The majority of participants still lacked the relevant qualifications required while the need for staff development was identified by many as a major concern. In the second part respondents overwhelmingly indicated the need for clarification on the nature, the role and functions of the education district. In the third part the report shows thata general agreement also exists amongst the respondents for the need to address the constraints experienced at all levels in the implementation of district support services. The study concludes that in a globally competitive environment like the one we have today, it is no longer sufficient to make excellent strategic and operational plans. It is rather crucial for organisations to have systems that will ensure that this plans are effectively achieved. The rationale for this view is based on the argument that this may provide opportunities for learners to extend and develop their personal education competence, critical awareness and shared insight of the role which they and schools are expected to fulfil in their rapidly changing communities. The following key concepts were used throughout the study: • Education District • Curriculum 2005-08-24 Education Policy Reserve Fund Programme (EPRFP) • The School Governing Body (SGB) • National Policy • District Support Services • Effective Teaching and Learning
Ph. D. (Curriculum Studies)
Department of Curriculum Studies and Education Management
Keywords: UCTD; 379.68257; Education and state -- South Africa -- Limpopo; Effective teaching -- South Africa -- Limpopo